Fibronectin as an enhancer of nonopsonic phagocytosis of Pseudomonas aeruginosa by macrophages. - Kluftinger, J L (1989)
Fibronectin is capable of enhancing uptake by macrophages of Pseudomonas aeruginosa grown in vivo in rats or mice or in vitro on nutrient agar plates. It was demonstrated that concentrations as low as 27 nM fibronectin produced significant enhancement of macrophage phagocytosis. Washing of fibronectin-treated macrophages did not prevent phagocytosis enhancement, but washing of fibronectin-treated bacteria did. The tetrapeptide arginine-glycine-aspartic acid-serine, which comprises the eucaryotic cell-binding domain of fibronectin, was also capable of promoting bacterial uptake, whereas the control tetrapeptide tetraglycine was not. Fibronectin caused depolarization of the mouse macrophage cell line P388D1, plasma membrane, as demonstrated by using a polarization-sensitive fluorescent probe. These data indicate that promotion by fibronectin of nonopsonic phagocytosis is mediated by the action of fibronectin on the macrophages.